War on Gaza - Sacco, Joe (Fantagraphics Books, 2024)
Joe Sacco is well known as an unflinching chronicler of the injustice inflicted on the Palestinian people (Palestine, 1993; Footnotes in Gaza, 2010). He continues this mission with War on Gaza, a series of graphic commentaries on Israel's rampage that began more than a year ago and continues relentlessly today. Published in installments on The Comics Journal's website, War on Gaza is a series of comics and single-panel illustrations that lay bare the naked immorality of the "war" itself and its dire and tragic consequences. Employing his trademark combination of honesty, compassion, and dark humor, Sacco's War on Gaza is an uncompromising critique of Israel's genocide and the complicity of President Joe Biden and the United States.